Immigrants Through the Eyes of Citizens of Kazakhstan: The Attitude of the Host Society to the Immigrants’ Health - Aidos Bolatov; Adil Samekin; Nazym Bozymbayeva; Assylkhan Bekbayev (Journal of Central Asian Studies)
This article examines the attitudes of Kazakhstani citizens towards health problems among immigrants. Respondents (N=401) from different regions of Kazakhstan took part in the study in 2023. According to the results of the study, it was found that (1) male respondents demonstrated significantly higher engagement with news about migrants compared to females. (2) Age and level of education were not associated with news engagement. (3) The probability of emigration correlated negatively with age but positively with education level, and positively with frequency of following migration news. (4) Individuals with conservative ideological orientations and liberal economic perspectives were more likely to follow migration news. (5) Attitudes towards immigrant health varied, with the majority supporting continuous health monitoring but divided opinions on whether immigrants pose a danger to public health. (6) Socio-demographic factors such as language, gender, experience living abroad, and ideological orientation influenced attitudes toward immigrant health. Therefore, understanding the complex attitudes of citizens towards immigrant health issues is essential for developing targeted interventions and policies that promote integration and address the diverse needs of both immigrants and the host population in Kazakhstan.